المعوقات البحثية لطلبة العلاقات العامةوعلاقتها بطبیعة البحوث المنتجة دراسـة مسحية - محمد, لانه‌ صابر (Sulaimani Journal for Humanities, 2018)
The problem of the current research is to investigate the obstacles facing public relations students during their scientific research. It aims at uncovering the nature of the research obstacles faced by students that affect the quality of productive research. The descriptive approach was used to reach the results. With the current research community represented by students of the Public Relations Branch of the Department of Information at the Faculty of Human Sciences at the University of Sulaymaniyah. The research found a number of results, the most important of which is that the language barrier is one of the most common problems faced by public relations students during their writing research.